Method for Improving the Efficiency of Simulation of ICT and BP Systems by Using Fast and Detailed Models - Muka, L.; Lencse, G. (Acta Technica Jaurinensis, 2012)
This paper describes how the fast and detailed modelling and simulation methods can be used to increase the efficiency of simulation of interconnected ICT (Information and Communication Technology) and BP (Business Process) systems. The method of cooperating models using detailed, fast and contracted fast models to model the functioning of ICT and BP is presented. A new approach, the diversified assignment method is described for the selection of the appropriate, efficient modelling and simulation method taking into account the criticality of the systems and the phase of simulation (preliminary and detailed). A system of cooperation of fast and detailed models is introduced for the preliminary and detailed phases of simulation and for the basic ICT-BP model configurations (ICT-BP focus).